A obra ficcional de Sérgio Milliet : marcas autobiográficas na narrativa Roberto (1935) - Santos, Maria da Conceição (2022)
Autobiography, as described in this work, corresponds to a textual or literary genre that features numerous shapes and developments, which makes the attempt to find a fixed definition into something slippery and fluctuating. Under this bias, this literary-discursive genre is considered, by many critics, a hybrid genre, in view of its flexible character with regard to breaking the ties of traditional literary referentiality. That said, this dissertation seeks to identify the autobiographical marks present in the narrative Roberto, through a critical-literary investigation, as a form of memorialistic search and identity discovery of SérgioMilliet. However, the discussions will be based, in addition to the theories presented, on the “autobiographical pact” of Philippe Lejeune, for though the literary work presents numerous aspects that associate Milliet with Roberto, the narrative is not an autobiography, for reasons that are discussed in this work. In terms of structure, this dissertation is divided into three chapters. In the first, we present the biobibliographic profile of SérgioMilliet. In the second, in the light of the theories of Antonio Candido and his workA personagem de ficção(The fictional character) (2009), we analyze the constitutive elements of the narrative Roberto, examining the composition of the characters, space and time. Finally, in the third and last chapter, the autobiographical aspects of the narrative are analyzed, intersecting fiction and reality, the main objective of this work. This last chapter is divided into three sections: “Childhood”, “Adolescence” and “Participation and political engagement in the 1930s”, so that autobiographical marks can be outlined in such sections, with regard to Roberto, in a more organized and precise way. To support the discussions in this chapter, we established a dialogue between the literary work and the two volumes of the memory book De ontem, de hoje, de sempre (Yesterday, today, always) (1960 – 1962).